Artificial Intelligence is Not God: Between Academic Ethics and the Worship of AI in Academic Publications at Islamic Universities - Jusri Pohan, Ali; Nasution, Suryadi (UIR Press, 2025)
This study examines the phenomenon of artificial intelligence (AI) usage in academic publications at Islamic universities, focusing on the implications for academic ethics and spiritual values. Using a qualitative case study approach, data were collected from 150 students and 25 lecturers at both public and private Islamic universities in North Sumatra through in-depth interviews, observations, and document analysis. The findings reveal that AI is often perceived as an instant solution capable of replacing human intellectual processes, leading to a phenomenon of